The characteristics of androgen receptor splice variant 7 in the treatment of hormonal sensitive prostate cancer: a systematic review and meta-analysis - Wang, Zhize (Cancer Cell Int, 2020)
BACKGROUND: Accumulating evidence suggests androgen receptor splice variant 7 (AR-V7) may be associated with the prognosis of castration-resistant prostate cancer (CRPC) received novel hormonal therapy while its characteristic and prognosis value in hormonal sensitive prostate cancer is unclear. METHODS: We aimed to evaluate the prognostic role of AR-V7 by progression free survival (PFS) and overall survival (OS) in hormonal sensitive prostate cancer (HSPC), and the AR-V7-positive-proportion difference in HSPC and CRPC. A search of PubMed, Embase, and the Web of Science was performed using the keywords prostate cancer, prostate tumor, prostate neoplasm, prostate carcinoma; AR-V7, AR3, androgen receptor splicing variant-7, or androgen receptor-3. Seventeen trials published due December 2019 were enrolled. RESULTS: AR-V7-positive proportion in CRPC was significantly larger than newly diagnosed prostate cancer (PCa) (odds ratio [OR] 7.06, 95% confidence interval [CI] 2.52–19.83, P < 0.001). Subgroup analyses indicated significantly higher AR-V7-positive proportion in CRPC derived from RNA in situ hybridization (OR 65.23, 95% CI 1.34–3171.43, P = 0.04), exosome RNA (OR 3.88, 95% CI 0.98–15.39, P = 0.05) and tissue RNA (OR 10.89, 95% CI 4.13–28.73, P < 0.001). AR-V7-positive patients had a significantly shorter PFS than those who were AR-V7-negative treated with first-line hormonal therapy (hazard ratio [HR] 3.63, 95% CI 1.85–7.10, P < 0.001) and prostatectomy (HR 2.49, 95% CI 1.33–4.64, P = 0.004). OS (HR 5.59, 95% CI 2.89–10.80, P < 0.001) were better in AR-V7-negative than AR-V7-positive HSPC patients treated with first-line hormonal therapy. The limitations of our meta-analysis were differences in study sample size and design, AR-V7 detection assay, and disease characteristics. CONCLUSION: AR-V7-positive proportion was significantly higher in CRPC than that in newly diagnosed PCa. AR-V7 positive HSPC patients portend worse prognosis of first-line hormonal therapy and prostatectomy. Additional studies are warranted to confirm these findings.